Factors influencing college students’ learning intention to online teaching videos during the pandemic in China - Hao, Yinhua; Zeng, Xiangmin; Yasin, Megat Al Imran; Boon Sim, Ng (SAGE Publications, 2024)
To explore the influencing factors of college students’ learning intention to online teaching videos during the pandemic, this study considered 696 college students from Huangshan University in China. The T-test and ANOVA were utilized to analyze gender, grade, and discipline on college students’ learning intention, and the regression analysis was utilized to explore four aspects including performance expectancy, effort expectancy, social influence, and facilitating conditions on college students’ learning intention. The results indicate the following: first, using descriptive analysis, it is observed that college students did not exhibit a positive learning attitude toward online teaching videos during the pandemic. Second, the t test and one-way analysis of variance indicate that grades between freshmen and seniors significantly influence the learning intention of college students to online teaching videos, whereas genders and disciplines do not. Third, through regression analysis, it is observed that performance expectancy, effort expectancy, social influence, and facilitating conditions significantly influence college students’ learning intention to online teaching videos. This study stipulates the following research proposals: resource construction, the optimization of the online teaching environment, advanced technology and psychological counseling. It is expected that the findings will provide references for studies on online teaching resources and online learning.